Stokely Speaks from black power to Pan-Africanism - Carmichael, Stokely (Chicago Chicago Review Press, 2007)
In the speeches and articles collected in this book, the black activist, organizer, and freedom fighter Stokely Carmichael traces the dramatic changes in his own consciousness and that of black Americans that took place during the evolving movements of Civil Rights, Black Power, and Pan-Africanism. Unique in his belief that the destiny of African Americans could not be separated from that of oppressed people the world over, Carmichael's Black Power principles insisted that blacks resist white brainwashing and redefine themselves. He was concerned not only with racism and exploitation, but with cultural integrity and the colonization of Africans in America. In these essays on racism, Black Power, the pitfalls of conventional liberalism, and solidarity with the oppressed masses and freedom fighters of all races and creeds, Carmichael addresses questions that still confront the black world and points to a need for an ideology of black and African liberation, unification, and transformation.
Keywords: Pan Africanism